'Thank You for Your Service:' Mapping Counter-memories as a Form of Spiritual Care Support for Moral Injury. Issue 1 (2nd January 2018) - Morris, Joshua T.
Abstract : The stories we tell about war produce the narrative of what war is. "Thank you for your service" becomes merely a symptom of a broader problem, and further, reveals a gap in the production of knowledge. The produced war memory risks exacerbating the trauma experienced by service members who do not fit the encoded narratives of "thank you for your service." A Foucauldian counter-memory helps produce a more robust memory, and in these counter-memories, we privilege voices on the margins. Therefore, how might spiritual care providers help co-create counter-memories?